2014
DOI: 10.1038/bjc.2014.578
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preset sequential administrations of sunitinib and everolimus on tumour differentiation in Caki-1 renal cell carcinoma

Abstract: Background:Sunitinib (VEGFR/PDGFR inhibitor) and everolimus (mTOR inhibitor) are both approved for advanced renal cell carcinoma (RCC) as first-line and second-line therapy, respectively. In the clinics, sunitinib treatment is limited by the emergence of acquired resistance, leading to a switch to second-line treatment at progression, often based on everolimus. No data have been yet generated on programmed alternating sequential strategies combining alternative use of sunitinib and everolimus before progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…This suggests that the drugs are effective when taken simultaneously or sequentially based on the reduction in the expression levels of the proteins and complexes. However, toxicity becomes a concern in the simultaneous intake case as already investigated in the previous studies 38. This suggests that the proposed sequential or switched drug inputs approach is a promising solution.…”
Section: Simulation Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…This suggests that the drugs are effective when taken simultaneously or sequentially based on the reduction in the expression levels of the proteins and complexes. However, toxicity becomes a concern in the simultaneous intake case as already investigated in the previous studies 38. This suggests that the proposed sequential or switched drug inputs approach is a promising solution.…”
Section: Simulation Resultsmentioning
confidence: 82%
“…Experimental data have suggested that MTDs for combination therapy drugs are different from those of monotherapy in which the drugs are given sequentially or individually35,8 and toxicity of drug combinations are higher than single-drug treatments. The model presented in this work is based on some previous studies 38.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The underlying rationale for drug combination treatment in cancer has been to coadminister drugs that act by different mechanisms, thereby increasing tumor cell killing while reducing the likelihood of drug resistance (Al-Lazikani et al, 2012). To rapidly move drug combinations to the clinic, studies need to compare the effects of simultaneous versus sequential administration of targeted therapy and select the best approach based on a solid mechanistic justification (Wang et al, 2012(Wang et al, , 2013Fung et al, 2013;Wild et al, 2013;Dos Santos et al, 2015;Song et al, 2015). If sequential administration is as effective as simultaneous administration, existing clinical trial toxicity data can be used to expedite clinical testing.…”
Section: Discussionmentioning
confidence: 99%